2014
DOI: 10.1007/s00044-014-1257-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacophore modeling, virtual screening, and 3D-QSAR studies on a series of non-steroidal aromatase inhibitors

Abstract: Aromatase inhibitors are the most important targets in treatment of estrogen-dependent cancers. In order to search for potent non-steroidal aromatase inhibitors (NSAIs) with lower side effects and overcome cellular resistance, Genetic Algorithm with Linear Assignment of Hypermolecular Alignment of Database was used to derive 3D pharmacophore models. The obtained best pharmacophore model contains one acceptor atom, one donor atom, and two hydrophobes, which was used in effective alignment of dataset. In success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Adhikari et al (2017[ 1 ]) performed an extensive study employing a wide range of QSAR models including 2D and 3D QSAR as well as molecular docking to also confirm the importance of the electrostatic property of the nitrogen-containing azole moiety, p -cyanophenyl moiety, p -nitrophenyl, hydro-phobicity as well as the appropriate size and shape of AIs were crucial for aromatase inhibitory activity. Xie et al (2015[ 105 ]) performed both CoMFA and CoMSIA studies and both studies further supported the importance of bulky steric groups as well as the importance of electrostatic properties pertaining to the presence of azole nitrogen atoms.…”
Section: Insights From Qsar Modelsmentioning
confidence: 95%
See 2 more Smart Citations
“…Adhikari et al (2017[ 1 ]) performed an extensive study employing a wide range of QSAR models including 2D and 3D QSAR as well as molecular docking to also confirm the importance of the electrostatic property of the nitrogen-containing azole moiety, p -cyanophenyl moiety, p -nitrophenyl, hydro-phobicity as well as the appropriate size and shape of AIs were crucial for aromatase inhibitory activity. Xie et al (2015[ 105 ]) performed both CoMFA and CoMSIA studies and both studies further supported the importance of bulky steric groups as well as the importance of electrostatic properties pertaining to the presence of azole nitrogen atoms.…”
Section: Insights From Qsar Modelsmentioning
confidence: 95%
“…Additionally, the increase in popularity of QSAR models for predicting AIs was greatly observed in 2011-2015 (Narayana et al, 2012[ 65 ]; Kishore et al, 2013[ 44 ]; Nantasenamat et al, 2013[ 61 ][ 64 ], 2014[ 63 ]; Dai et al, 2014[ 25 ]; Xie et al, 2014[ 104 ]; Worachartcheewan et al, 2014[ 101 ][ 103 ]; Shoombuatong et al, 2015[ 85 ]; Awasthi et al, 2015[ 7 ]; Xie et al, 2015[ 105 ]; Kumar et al, 2016[ 48 ]) whereby the number of publications increased to thirteen, with an even more dramatic rise in the number of compounds used for calculating descriptors using LOO-CV and external validation (Figure 5 (Fig. 5) ).…”
Section: Qsar Models Of Aromatase Inhibitory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Two techniques are commonly used for the global application of the predictive modeling in toxicology, for example, employing either a large dataset using techniques such as machine learning methods or deriving mechanistically interpretable simple models [14,15]. Both techniques have been exploited to create predictive models for the antagonist activity of azoles with CYP19A1 [16][17][18][19][20]. Shoombuatong et al, 2018, reviewed this area and concluded that the modeling of nonsteroidal aromatase inhibition requires nitrogen-containing descriptors, polarizability, the energy of highest occupied molecular orbital (HOMO), the energy gap of highest occupied molecular orbital and lowest unoccupied molecular orbital (HOMO-LUMO gap), and descriptors for hydrogen bond acceptors [21].…”
Section: Or 4 Respectively) Present Inmentioning
confidence: 99%
“…Although their effectiveness is superior to that of Tamoxifen, which is the most used drug in endocrine therapy in ER+ breast cancer, the search for novel classes of AIs is still required because of their side effects, such as bone loss and cardiovascular disease, and of the potential resistance occurrence due to prolonged use. The discovery of potent nonsteroidal aromatase inhibitors (NSAIs) provided with fewer side effects and cell resistance is thus extremely pursued [7,8]. The triazole ring system replacement and the proper functionalization of additional aromatic/cyclic moieties represent suitable strategies for addressing a more selective inhibition towards the aromatase enzyme.…”
Section: Introductionmentioning
confidence: 99%